Case report of the treatment and experience of mental disorders due to chronic viral encephalitis. Issue 1 (13th January 2021) - Zheng, Mingming; Bi, Ran; Lin, Yezhe; Zhu, Cuizhen; Zhu, Daomin
Abstract : Viral encephalitis is a common clinical condition. Its clinical manifestations are variable and include neurological symptoms and psychiatric abnormalities, which makes clinical diagnosis and treatment difficult. To date, there are only a few reported cases on mental symptoms of chronic viral encephalitis. We present a case of a 16-year-old male patient who was previously hospitalised and diagnosed with schizophrenia and treated with aripiprazole 15 mg/day but failed to respond. The patient was then given antiviral therapy and recovered after 2 weeks. Clinicians should be aware of the possbility that chronic mental disorders could be caused by viral encephalitis. In the future, diagnosis of chronic functional mental disorders should include viral encephalitis in the differential diagnosis.